Implementasi Implementasi Peraturan Desa Untuk Meningkatkan Civic Engagement Masyarakat - Fandi, Fandi Zahri; Erwin; Purnama, Shilmy; Bistari; Sastra Atmaja, Thomy (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2023)
Village regulations are legal products that have their own position in the life of village communities as guidelines for the administration of village government. There is a lack of development facilities that are suitable for the village environment to support the community, thus encouraging the creation of village regulations. The aim of the research is to find out a picture of the implementation of village regulations towards increasing community civic engagement. The research method used is a qualitative approach through observation, in-depth interviews with the community, community institutions and village government and documentation. The results of the research show that the implementation of village regulations on community civic engagement takes the form of implementation of village regulations by building facilities and infrastructure in the form of roads and banjars, bridges, irrigation and water gates, as well as installing street lighting. Description of the implementation of the community being able to contribute, build organization, take action or take action, motivate and be responsible for implementing village regulations. There is a need to increase communication, education and the use of technology to help increase community involvement. Thus, it is hoped that this research will be able to contribute to further understanding of the implementation of village regulations to increase community civic engagement.